State Regulation of Housing and Communal Services of the Russian Federation: Centralization of Management or Market Self-Regulation - V. I. Belov (Управленческое консультирование)
This article discusses the proposed measures of the Ministry of Construction and Housing and Communal Services of the Russian Federation, set out in the draft strategy for the development of the construction industry and housing and communal services, which received a disapproving response from some experts in the media. The article analyzes the regulatory documents regulating the activities of management organizations in the housing and communal services market. According to the results of the analysis carried out by the author, it was found that state regulation of the industry in question only through laws and by-laws is currently insufficient. The initiative of the Ministry of Construction of the Russian Federation related to the introduction of a regional operator (guaranteeing management organization) into business practice is justified by the author of the article from an organizational, managerial, and economic point of view. In particular, it is proposed to expand the subject-object relations between the state and the management organization in the management system to subject-subject relations between the regional operator (guaranteeing management organization) and consumers of housing and communal services. From an economic point of view, the proposals of the Ministry of Construction of Russia may be economically beneficial for both sides: the state receives a large return on budgets of different levels by changing the taxation system (from simplified to general) and the corresponding tax rate, and management organizations receive a large profit by increasing the profitability of their professional activities by 1.5–2 times. As a result, the author comes to the conclusion that the measures proposed by the Ministry of Construction of Russia are necessary and non-discriminatory, since the relationship between the management organization and consumers of housing and communal services is carried out on market principles and in a competitive environment, and the administration of processes by the state regarding the selection of management organizations for the provision of housing and communal services to the population does not infringe on the rights of economic entities to carry out any legitimate economic activity.